Analysis of Vegetable Supply Chain Management at PT. Bumi Nyiur Swalayan Palu - Elmi Jusmelya; Suryadi Hadi; Sulaeman Miru; Cici Rianty (The Journal of Management, Digital Business, and Entrepreneurship, 2024)
This study aims to understand the supply chain management practices in the fresh retail sector, especially at PT. Bumi Nyiur Swalayan Palu City, Central Sulawesi. The main focus of this study is on the supply chain management of vegetable products that have perishable characteristics and require special handling such as Cold Chain Logistics (CCL). Using a qualitative descriptive approach, data were collected through direct observation and in-depth interviews with three key informants involved in supply chain management. The results of the study indicate that the application of the Supply Chain Operations Reference (SCOR) method contributes significantly to increasing operational efficiency and customer satisfaction. The five main elements of SCOR - planning, procurement, production, delivery, and returns - are implemented in an integrated manner to maintain product quality and freshness. This study also found that the success of the supply chain is determined by the coordination and collaboration between local farmers, market collectors, and hydroponic producers. PT. Bumi Nyiur Swalayan implements a management control system based on managerial functions in managing the flow of products, finances, and information in the supply chain. The flow of products is carried out from upstream to downstream, while the flow of finances and information moves reciprocally to ensure transparency and timeliness of delivery. FIFO techniques and quality monitoring are carried out to maintain the freshness and quality of products. This study concludes that structured and adaptive supply chain management is key to maintaining the competitiveness of fresh retail businesses amidst the challenges of dynamic consumer demand.